Rural Tourism Development in Gujarat: Views of the Stakeholders (Vallis Aurea, 2023)
Purpose: Sustainable Tourism development in the rural region has become a must which includes the interests of all stakeholders, along with tourism promotion and tourism growth. This study aims to identify the opinion of stakeholders to achieve sustainable rural tourism development.Design: Exploratory Research and descriptive research.Methodology & Approach: Qualitative and Quantitative. Primary data was collected through in-depth interviews and surveys. A structured questionnaire was used as an instrument. The non-probability sampling procedure is used. The sample size of the Community is 262 and of Tour operators is 167.Findings: It has been found that there should be the development of a regional tourism workforce and infrastructure, the introduction of home stay policy, the promotion of a tourism-friendly atmosphere, showcasing Gujarat beyond God and spirituality and the creation of multiple activities in rural areas.